ANALISIS TINGKAT MINAT SISWA TERHADAP MATA PELAJARAN PENDIDIKAN JASMANI DAN OLAHRAGA KESEHATAN (PJOK) DI SDN 2 SUKARAME - Anisa Nurfauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interest in learning is an important factor that influences the success of the learning process, including in the subject of Physical Education, Sports, and Health. Based on the results of observations at SDN 2 Sukarame, it was found that not all students showed active involvement and optimal interest in participating in Physical Education, Sports, and Health learning, so an analysis of the level of student interest is needed. This study aims to determine the level of student interest in Physical Education, Sports, and Health subjects at SDN 2 Sukarame. The results showed that the overall level of student interest was in the positive category, The results showed that the level of student interest in Physical Education, Sports, and Health subjects was in the high category with a result of 70%, it was concluded that the majority of students had a high interest in Physical Education, Sports, and Health, so it is recommended for teachers to continue to maintain this interest through interesting learning strategies and pay more attention to students who are still in the moderate interest category so that their learning motivation can increase optimally.